Performance Of Land Office Employees In South Tangerang City: The Role Of Work Motivation, Work Discipline And Competence In Work Effectiveness - Hamsinah, Hamsinah; Irawan, Sani; Wahyudi, Wahyudi (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2025)
The purpose of this study is to determine the Performance of Employees of the South Tangerang City Land Office: The Role of Work Motivation, Work Discipline and Competence in Work Effectiveness. The method in this study is quantitative research, assessment based on numbers using statistical calculations, using the Simple Random Sampling technique. This study used a sample of 105 respondents. Data is processed using the SEM PLS 3.0 method. The results of the study indicate that 1) the motivation variable (X1) directly has a positive and significant effect on work effectiveness (Y) with a t-statistic value of 2.588 > t-table 1.982 and a P-value of 0.010 < 0.05. 2) The work discipline variable (X2) directly does not have a significant effect on work effectiveness (Y) with a t-statistic value of 0.508 < 1.982 and a P-value of 0.611 > 0.05. 3) The competency variable (X3) directly does not have a significant effect on work effectiveness (Y) with at statistical value of 0.274 < 1.982 and a P-value of 0.784 > 0.05, 4) the Motivation variable (X1) directly has a significant effect on employee performance (Z) with at statistical value of 0.465 < 1.982 and a P-value of 0.642 > 0.05, 5) the work discipline variable (X2) directly has a positive and significant effect on employee performance (Z) with at statistical value of 2.296 > t table 1.982 and a P-value of 0.022 < 0.05. 6) Competence (X3) directly does not have a significant effect on employee performance (Z) with a statistical value of 0.615 < 1.982 and a P-value of 0.539 > 0.05. 7) Work effectiveness (Y) has a direct and significant effect on employee performance (Z) with at statistical value of 3.092 > t table 1.982 and a P-value of 0.002 < 0.05. 8) Motivation variable (X1) indirectly has a significant effect on employee performance (Z) through work effectiveness (Y) with at statistical value of 2.245 > t table 1.982 and a P-value of 0.025 < 0.05, 9) work discipline variable (X2) indirectly does not have a significant effect on employee performance (Z) through work effectiveness with at statistical value of 0.445 < 1.982 and a P-value of 0.656 > 0.05. 10) Competence (X3) indirectly does not have a significant effect on employee performance (Z) through work effectiveness (Y) with a statistical value of 0.235 < 1.982 and a P-value of 0.815 > 0.05.